Fat activism: A radical social movement by Charlotte Cooper - Cassandra Kuyvenhoven (Canadian Food Studies, 2016)
In Fat Activism, Cooper responds to mainstream and scholarly writings on fat activism that she claims create negative assumptions or “proxies” of fat people. These constructed proxies serve to efface, reduce, and oversimplify the voices and the lived experiences of fat activists and fat activism. Through proxies, fat people are further marginalized and estranged from writings about what it means to be fat and what it means to be an activist. In this context, fat is a descriptive word that rejects medicalized terminology and encompasses non-normative embodiments of adipose tissue. Fat is not a bad word: it is powerful, political, and not without controversy.